2006
DOI: 10.1590/s0103-90162006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplasma associated with shoot proliferation in begonia

Abstract: Begonia is a very appreciated genus of ornamental plants, of economic relevancy, having species of flowers and foliage. In commercial croppings, plants exhibiting characteristic symptoms of phytoplasma infection have been observed, such as shoot proliferation, reduced plant, size small leaves and flowers, and phyllody. Leaves were sampled and total DNA was extracted to be used in nested Polymerase Chain Reaction (PCR), in order to detect and identify an expected phytoplasma. The results confirmed consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although phytoplasmas of the 16SrI (aster yellows) group have frequently been found in plants in countries of the Northern hemisphere that (Montano et al 2006), and other species such as China tree (Duarte et al 2009), begonia (Ribeiro et al 2006), and Celosia argentea and Celosia spicata (Eckstein et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although phytoplasmas of the 16SrI (aster yellows) group have frequently been found in plants in countries of the Northern hemisphere that (Montano et al 2006), and other species such as China tree (Duarte et al 2009), begonia (Ribeiro et al 2006), and Celosia argentea and Celosia spicata (Eckstein et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A new phytoplasma was identifi ed as infecting Cassia italica in Oman(Al-Saady et al 2008 ) Siddique ( 2006 ). reported phyllody on Gerbera jamesonii in Australia, whileRibeiro et al ( 2006 ) reported shoot proliferation in Begonia in Brazil Jones and Arocha ( 2006 ). reported yellowing and littleleaf disease on Veronica scutellata in the United Kingdom.Al-Zadjali et al( 2007 )identifi ed and molecularly characterized the phytoplasma associated with Jasminum sambac witches' broom in Oman Sobolev et al ( 2007 ).…”
mentioning
confidence: 99%